Photoelctrochemically Manufactured HgO/Cu2O Monolayer with Ameliorate Photovoltaic Features - Abdurrahman, Muhammad; Burari, F. W.; Olasoji, O. W. (Computational And Experimental Research In Materials And Renewable Energy, 2022)
This writing report acquaint the chances for promoting efficiency betterment of p-Cu2O electrode for PECs likewise in production of hydrogen gas, using HgO/Cu2O hetero-structure. The arrangement was accomplished by both bracing the surface of p-Cu2O plate embattled through thermal oxidization of copper sheet and also acquiring low cost, effortless and low impairment engineering deposition for utilizing HgO as absorber layer. The altitudinous efficiency of 4.80% and open circuit voltage of 185MV were incurred in an HgO/Cu2O hetero-structure PEC solar cell commence with copper foil thickness (0.1mm) substrate for preparing the Cu2O thin film under oxygen gas pressure at 950℃ by thermal oxidizing techniques. It is requisite to augmented the interface at the hetero-structure junction to accomplished a soaring efficiency in HgO/Cu2O/HgO semiconductor beside multiplicative the parallel resistance and remittent the series resistance.Keywords: thermal oxidation, cuprous oxide, hetero-structure, J-V characteristic, photoelectrochemical, annealing, etching.